Różnorodność cechą współczesnego świata - Zawadzka-Bartnik, Elżbieta (Neofilolog, 2011)
This paper deals with cultural, ethnic, religious, physical and mental diversi-ty as well with different preferences of value systems, lifestyles, etc. domi-nating in contemporary societies and presents the resulting educational im-plications. Because of the specificity of social perception, every single case of variation/strangeness triggers off the process of stigmatization/labelling, manifesting itself in intolerant, discriminating or even hostile behaviour. The paper indicates the negative influence of the so-called „hidden pro-gramme” of the school and emphasizes the need for increased educational efforts aimed at the formation of tolerant attitudes among students.